Case report: Long-term management of occlusion after surgical-orthodontic treatment for a patient with drug-induced open bite developed after the onset of schizophrenia - Takada, Jun-Ichi; Higashihori, Norihisa; Kadota-Watanabe, Chiho; Kawamoto, Tatsuo; Toyofuku, Akira; Moriyama, Keiji (Frontiers in Psychiatry, 2023)
Background Schizophrenia is a major mental disorder, with an estimated incidence of 1%. Since they are sensitive to sensory changes, orthodontic treatment to move teeth should be avoided as aggressively as possible in these patients because of strong concerns about the possibility of causing adverse psychological effects, thus there are few reports on orthodontic treatment for schizophrenia patients. We report a case of severe open bite caused by medication after the onset of schizophrenia, even though the patient’s occlusion had been stable for a long time after surgical orthodontic treatment. Medication control and the use of a minimally invasive orthodontic appliance improved the occlusion without adversely affecting the patient’s mental health. Case A 22-year-old woman presented to the clinic with a chief complaint of an anterior open bite. Intraoral findings showed an overbite (vertical overlap of the incisor teeth) of −3.0 mm and an overjet (horizontal overlap of the incisor teeth) of −0.5 mm. The preoperative orthodontic treatment included bilateral extraction of the maxillary first premolars. Subsequently, orthognathic surgery was performed to achieve a harmonized skeletal relationship and occlusion. Occlusion was stable for 3 years after surgery. However, 10 years after surgery, the patient returned to the clinic complaining of an anterior open bite (overbite = −4.0 mm). Six years prior to the return, the patient was diagnosed with schizophrenia. We thought that ignoring the patient’s strong desire to treat her open bite might also cause psychological problems; therefore, in addition to medication control, we treated her using a minimally invasive removable orthodontic appliance (retainer with tongue crib). Her anterior open bite improved (overbite, +1.0 mm) to within the normal range. Conclusion In this case, medication control was thought to be essential to improve her drug-induced open bite. However, minimally invasive orthodontic treatment, such as the use of a removable appliance, might be helpful in promoting her mental stability as well as for improving occlusion. Careful support is required to obtain information about the patient’s mental state and medications through close cooperation with psychiatrists.